(untitled) (Comparative Professional Pedagogy, 2021)
The article deals with the scientific issue of using interactive methods in the system of patriotic education for future naval specialists in the context of foreign scholars’ views. It shows that given today’s historical and socio-economic conditions, it is vital to abandon excessive ideology and ideological monopoly, schematism and formalism in the educational process, implement more effective educational technologies and, most importantly, create a new system of forming patriots using interactive methods. The article proves that since interactive methods enhance pedagogical interaction, communication, exchange of activities and their diversity, they manage to improve the behaviour and activities of naval cadets towards patriotic education. It also indicates that the introduction of interactive and communicative forms of personality-oriented education in patriotic education of naval cadets mostly depends on the invariants of personality-oriented approach to the educational process. It is because naval students choose moral norms, values, lifestyles and thus acquire positive personal experience through their participation in such forms of learning. A prerequisite for fulfilling the goals of patriotic education is appropriate methodical training of university teachers. However, there are no original methods characteristic of especially patriotic education of students. One cannot develop students’ patriotic feelings, patriotic identity, spirituality, culture, independence, initiative, and sociality socialize with traditional methods only. In this regard, some scholars believe that interactive methods have proved to be most effective concerning patriotic education as interactivity enables interpersonal cognitive communication and interaction between all education stakeholders.